2008
DOI: 10.1007/s00449-008-0224-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid biological synthesis of silver nanoparticles using plant leaf extracts

Abstract: Five plant leaf extracts (Pine, Persimmon, Ginkgo, Magnolia and Platanus) were used and compared for their extracellular synthesis of metallic silver nanoparticles. Stable silver nanoparticles were formed by treating aqueous solution of AgNO(3) with the plant leaf extracts as reducing agent of Ag(+) to Ag(0). UV-visible spectroscopy was used to monitor the quantitative formation of silver nanoparticles. Magnolia leaf broth was the best reducing agent in terms of synthesis rate and conversion to silver nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
604
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,234 publications
(655 citation statements)
references
References 14 publications
42
604
2
7
Order By: Relevance
“…These processes involve several toxic chemicals as reducing agents. Because of using noble metal nanoparticles in areas of human contact 3 , there is an emergent need to develop eco-friendly biosynthesis processes that hinders the use of toxic chemicals. Recently, bio-green method using medicinal plant extract has gained the unique importance due to non-toxic and less time requirement in the synthesis of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…These processes involve several toxic chemicals as reducing agents. Because of using noble metal nanoparticles in areas of human contact 3 , there is an emergent need to develop eco-friendly biosynthesis processes that hinders the use of toxic chemicals. Recently, bio-green method using medicinal plant extract has gained the unique importance due to non-toxic and less time requirement in the synthesis of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The research on synthesized nanomaterials and their characterization is an emerging field of nanotechnology from the past two decades, due to their huge applications in the fields of physics, chemistry, biology and medicine [3] . Many techniques of synthesizing silver nanoparticles, such as chemical reduction of silver ions in aqueous solutions with or without stabilizing agents [4] , thermal decomposition in organic solvents [5] , chemical reduction and photoreduction in reverse micelles [6,7] , and radiation chemical reduction [8][9][10] have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Algae are otherwise called bionanofactories because they synthesized nanoparticles with high stability, are easy to handle, and eliminate cell maintenance (Song and Kim, 2009). Recently, gold nanoparticle synthesized using the extract of seaweeds such as Sargassum wightii (Singaravelu et al, 2007), Turbinaria conoides (Vijayaraghavan et al, 2011), Laminaria japonica (Ghodake and Lee, 2011), and Stoechospermum marginatum (Rajathi et al, 2012) was reported.…”
Section: Introductionmentioning
confidence: 99%